2021
DOI: 10.1111/gcb.15566
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas production and lipid biomarker distribution in Yedoma and Alas thermokarst lake sediments in Eastern Siberia

Abstract: Permafrost thaw leads to thermokarst lake formation and talik growth tens of meters deep, enabling microbial decomposition of formerly frozen organic matter (OM). We analyzed two 17-m-long thermokarst lake sediment cores taken in Central Yakutia, Russia. One core was from an Alas lake in a Holocene thermokarst basin that underwent multiple lake generations, and the second core from a young Yedoma upland lake (formed ~70 years ago) whose sediments have thawed for the first time since deposition. This comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 87 publications
(163 reference statements)
2
32
0
Order By: Relevance
“…Relatively few OM was deposited, which could then be decomposed comparatively quickly. Despite the low OC content of the Yukechi Yedoma IC sediments, Jongejans et al (2021a) found substantial greenhouse gas production from sediments upon thawing. Their findings showed that the OM quality and turnover history are the main driver for GHG production (Jongejans et al, 2021a).…”
Section: Organic Carbon Characteristics Of Thawed and Frozen Yedoma Deposits At The Yukechi Study Sitementioning
confidence: 87%
See 1 more Smart Citation
“…Relatively few OM was deposited, which could then be decomposed comparatively quickly. Despite the low OC content of the Yukechi Yedoma IC sediments, Jongejans et al (2021a) found substantial greenhouse gas production from sediments upon thawing. Their findings showed that the OM quality and turnover history are the main driver for GHG production (Jongejans et al, 2021a).…”
Section: Organic Carbon Characteristics Of Thawed and Frozen Yedoma Deposits At The Yukechi Study Sitementioning
confidence: 87%
“…Strauss et al (2017) calculated an amount of 398 Gt OC for the total circum-Arctic Yedoma domain (1.4 million km 2 , including thermokarst lakes and basins). However, recent carbon inventory studies of Central Yakutian Yedoma deposits show significantly lower levels of OC (Ø 0.4-0.7 wt%; Windirsch et al, 2020;Jongejans et al, 2021a).…”
Section: Introductionmentioning
confidence: 96%
“…The modern global net emission to the atmosphere is ~580 Tg CH 4 year −1 (He et al, 2020) and increasing by ~5 Tg CH 4 year −1 (Saunois et al, 2016). CH 4 is produced in the last step of anaerobic organic carbon reduction (methanogenesis; Megonigal et al, 2004) by various methanogenic archaea (including hydrogenotrophs, formatotrophs, acetotrophs, methylotrophs, and alcoholotrophs; Bridgham et al, 2013;Chen et al, 2013;Jongejans et al, 2021;McNicol et al, 2020;Serrano-Silva et al, 2014). In turn, CH 4 itself can serve as a carbon and energy source for specialized aerobic and anaerobic microorganisms (methanotrophs) in sediments and soils (see Knittel & Boetius, 2009;Serrano-Silva et al, 2014 for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…A significant portion of the Lake Malaya Chabyda sediment core is classified as organic sediment, which is predicted to lose comparatively high percentages of their OC upon potential exposure. Jongejans et al (2021) found that although the OC content of the Yukechi Yedoma ice complex sediments was relatively low, there was substantial greenhouse gas release upon thawing. These findings point to OM quality and decomposition history and more important drivers of greenhouse gas release than OM content alone (Jongejans et al, 2021).…”
Section: Lake Malaya Chabyda Carbon Accumulation Ratesmentioning
confidence: 98%